2017
DOI: 10.3389/fnbeh.2017.00113
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Sex-Dependent Vulnerability to Metabolic challenges in Prenatally Stressed Rats

Abstract: Prenatal stress (PNS) might affect the developmental programming of adult chronic diseases such as metabolic and mood disorders. The molecular mechanisms underlying such regulations may rely upon long-term changes in stress-responsive effectors such as Brain-Derived Neurotrophic Factor (BDNF) that can affect neuronal plasticity underlying mood disorders and may also play a role in metabolic regulation. Based upon previous data, we hypothesized that PNS might lead to greater vulnerability to an obesogenic chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 55 publications
4
28
0
Order By: Relevance
“…Although clinical studies show a clear correlation of gestational (Entringer, Buss, & Wadhwa, 2010;Goldstein et al, 2016) and childhood stress (Agardh, Allebeck, Hallqvist, Moradi, & Sidorchuk, 2011;Danese & Tan, 2014;Thomas, Hypponen, & Power, 2008) with metabolic risk, whether the effects of ELS can be accurately replicated in animal models remains unknown. In agreement with our results, several reports have shown that PNS causes fasting hyperglycemia in adults (Detka et al, 2014;Lesage et al, 2004;Paternain et al, 2013), without further affecting glucose tolerance (Panetta et al, 2017). However, only a few reports have addressed the effect of MS180 on metabolic risk (Ruiz et al, 2018;Solas et al, 2010;Vargas et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Although clinical studies show a clear correlation of gestational (Entringer, Buss, & Wadhwa, 2010;Goldstein et al, 2016) and childhood stress (Agardh, Allebeck, Hallqvist, Moradi, & Sidorchuk, 2011;Danese & Tan, 2014;Thomas, Hypponen, & Power, 2008) with metabolic risk, whether the effects of ELS can be accurately replicated in animal models remains unknown. In agreement with our results, several reports have shown that PNS causes fasting hyperglycemia in adults (Detka et al, 2014;Lesage et al, 2004;Paternain et al, 2013), without further affecting glucose tolerance (Panetta et al, 2017). However, only a few reports have addressed the effect of MS180 on metabolic risk (Ruiz et al, 2018;Solas et al, 2010;Vargas et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…This was interesting given the usual consensus that PNS combined with HF diet increases insulin resistance, overeating and obesity as suggested in some studies [16] , [57] . This may be again related to the window of intervention, since other studies focusing on different time-windows reported the opposite effect [12] , [51] , [58] . Altogether, while late gestation adversities appear to more profoundly affect females [14] , [15] , [16] and early gestation adversities appear to have more profound effects on males, whole pregnancy adversities appear to have strong and opposite effects for each sex, at least regarding metabolic responses to challenge.…”
Section: Discussionmentioning
confidence: 88%
“…Animals subjected to prenatal stress showed an increase in this behavior at prepubertal and adult stages (Peters, 1986, DeminiĂ©re et al, 1992, Martinez-Tellez et al, 2009). In addition, several reports have shown an increase in the response to the stress of these animals through tests, such as elevated plus maze (Muhammad & Kolb, 2011;Panetta et al, 2017). However, postnatal stress, such as stress produced by maternal separation, depending on the stage of separation, can cause a reduction in locomotor activity in a new environment at prepubertal age without changes at adult age (Monroy et al, 2010) or not produce changes in locomotor activity (Aya-Ramos et al, 2017;Li, Robinson, & Bhatnagar, 2003) or produce an increase in locomotion in a new environment to adulthood (Soztutar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%